Eastern and cross cultural management - Singh, N. K., 1937- (Management for professionals., 2012)
Based on both theory and extensive empirical research, this book is compares culture and management styles in India, Japan, China and Western countries, and proposes a synthesis of West-dominated management technology with Eastern intuition ...